Islamic universalism: Ibn Qayyim al-Jawziyya's Salafī deliberations on the duration of Hell-Fire - Hoover, Jon (Wiley, 2009)
Classical Sunni eschatology maintains that all those who believe that God is one will enter the Garden of Paradise in due time. Some monotheists may first have to endure punishment and purification in the Fire for their sins, but those with even the least grain of belief will eventually enter the Garden as their reward. Conversely, unbelievers and those who associate partners with God (mushrikūn) will spend eternity in Hell-Fire as retribution for their unforgivable error.1 Classical Sunnism supports punishment of unbelievers and associators in unending Fire with many verses from the Qur’ān. However, its fundamental warrant for this doctrine is not the Qur’ān but consensus (ijmā‘). The classical Sunni principle of consensus affirms that when the scholars of the Muslim community have agreed on a matter — that Islam has Five Pillars, for example — it is no longer open to discussion.2 So, the claim here is that the Muslim community has reached a binding consensus that punishment of unbelievers in the Fire will never cease.3